Strategic directions for human development in Papua New Guinea (Washington, D.C., 2007)
There is an emerging consensus in Papua New Guinea (PNG) - both at the governmental level and among civil society more generally - that human development outcomes are far less than provision of basic services in many parts of the country is failing. The book addresses the need to understand the underlying reason behind these sectors' poor performance and innovatively develop approaches for improving service delivery that fits with the country's economic, geographic, social, and cultural contexts. Strategic Directions for Human Development in Papua New Guinea presents the results of a joint venture among the World Bank, the Australian International Development Agency, the Asian Development Bank, and the Government of Papua New Guinea to conduct a situational assessment in the health, HIV/AIDS, and education sectors and suggest options to jointly move forward to improve human development outcomes. In addition, a series of cross - cutting issues common to all sectors is reviewed. Issus highlighted include the role of the public sector in delivering basic public services, the problems associated with the structure of decentralization and devolution arrangements, and the importance of having feasible financing, expenditure, and implementation plans that accurately reflect sectoral priorities. This book will be of particular interest to those working in the areas of public financing, health and HIV/AIDS, education, and public services infrastructure.
Keywords: Public investments,Education,Sức khỏe công cộng,HIV infections,Public health,AIDS (Disease); Finance,Tài chính,Prevention,Finance,Prevention; Papua New Guinea,Papua New Guinea,Papua New Guinea,Papua New Guinea,Papua New Guinea